吳汝綸日本教育考察與對晚清學制建立影響程度的再探討 Master Ju-Lun Wu's Inspection of Japanese Education and Reevaluation of Its Influence on the Drafting of School Systems in the Late Ch'ing Period - 周愚文 Yu-Wen Chou (National Taiwan Normal University, 2015)
中國教育西化始於晚清，而壬寅及癸卯學制則是創始，主要仿日。制定過程中，過去許多研究認為吳汝綸是主要影響人物之一，他在就任京師大學堂總教習前獲派赴日考察教育4個月，透過參觀、訪談、聽講及資料蒐集，希望全面深入瞭解日本教育的發展與問題。訪問結果除即時陳報管學大臣張百熙及相關人員外，另出版《東遊叢錄》供修訂癸卯學制參考。但經本研究再考察發現，因人在日本考察、返國後朝局不利及病逝等因素，故他未能直接參與規劃、引導方向，以致主政人員在設計學制時，仍只是複製日本制度而已。 The modernization of Chinese education began from the late Ch'ing period, and the 1902 Ren-yin and 1904 Kuei-mao school systems marked the beginning of the modernization of Chinese education, which borrowed from Japanese education. Numerous studies have claimed that master Ju-Lun Wu was one of the key figures, before he inaugurated the vice-chancellor of Imperial Capital University, who inspected Japanese education over 4 months. He inquired into the development and problems of Japanese education by inspecting schools and universities; discussing with scholars, educators, and officials; listening to lectures; and collecting materials. His findings were reported to Minister Pai-Shi Chang and related staff and his Collected Records of Visiting Japan was published. Although his book became a reference book, this study found that Ju-Lun Wu was not directly involved in drafting school systems for several reasons. Therefore, the 1904 Kuei-mao system remains an uncritical, imitated Japanese school system.